The Patient Health Questionnaire Anxiety and Depression Scale (PHQ-ADS): Initial Validation in Three Clinical Trials - Kroenke, Kurt (Psychosom Med, 2016)
OBJECTIVE: We examine the reliability and validity of the Patient Health Questionnaire Anxiety-Depression Scale (PHQ-ADS) – which combines the PHQ-9 and GAD-7 scales – as a composite measure of depression and anxiety. METHODS: Baseline data from 896 patients enrolled in 2 primary-care based trials of chronic pain and 1 oncology-practice based trial of depression and pain were analyzed. The internal reliability, standard error of measurement (SEM), and convergent, construct, and factor structure validity, as well as sensitivity to change of the PHQ-ADS were examined. RESULTS: The PHQ-ADS demonstrated high internal reliability (Cronbach's alpha of 0.8 to 0.9) in all 3 trials. PHQ-ADS scores can range from 0 to 48 (with higher scores indicating more severe depression/anxiety), and the estimated SEM was approximately 3 to 4 points. The PHQ-ADS showed strong convergent (most correlations 0.7-0.8 range) and construct (most correlations 0.4-0.6 range) validity when examining its association with other mental health, quality of life and disability measures. PHQ-ADS cutpoints of 10, 20, and 30 indicated mild, moderate, and severe levels of depression/anxiety, respectively. Bi-factor analysis showed sufficient unidimensionality of the PHQ-ADS score. PHQ-ADS change scores at 3 months differentiated (P < .0001) between individuals classified as worse, stable, or improved by a reference measure, providing preliminary evidence for sensitivity to change. CONCLUSIONS: The PHQ-ADS may be a reliable and valid composite measure of depression and anxiety which, if validated in other populations, could be useful as a single measure for jointly assessing two of the most common psychological conditions in clinical practice and research. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT00926588 (SCOPE); NCT00386243 (ESCAPE); NCT00313573 (INCPAD);